Visuo-Proprioceptive Matching Errors Are Consistent with Biases in Distance Judgments. Issue 5 (3rd September 2019) - Kuling, Irene A.; de Bruijne, Willem J.; Burgering, Kimberley; Brenner, Eli; Smeets, Jeroen B. J.
Abstract: People make systematic errors when matching the location of an unseen index finger with that of a visual target. These errors are consistent over time, but idiosyncratic and surprisingly task-specific. The errors that are made when moving the unseen index finger to a visual target are not consistent with the errors when moving a visual target to the unseen index finger. To test whether such inconsistencies arise because a large part of the matching errors originate during movement execution, we compared errors in moving the unseen finger to a target with biases in deciding which of two visual targets was closer to the index finger before the movement. We found that the judgment as to which is the closest target was consistent with the matching errors. This means that inconsistencies in visuo-proprioceptive matching errors are not caused by systematic errors in movement execution, but are likely to be related to biases in sensory transformations.